2012
DOI: 10.1007/s00296-012-2400-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and significance of the MEFV gene mutations in childhood Henoch–Schönlein purpura without FMF symptoms

Abstract: Familial Mediterranean fever (FMF) has been reported more frequently in patients presenting with Henoch-Schönlein purpura (HSP) than in the general population. But, there is no clear knowledge about MEFV mutations in patients with HSP. We investigated the prevalence of MEFV mutations in children with HSP and without FMF whether these mutations have any effect on the disease course or complications. A total of 76 children with HSP who had no typical symptoms of FMF were screened for the mutations in exon 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 17 publications
7
27
2
4
Order By: Relevance
“…This finding probably indicates that M680I mutation may be a predisposing factor to HSP. Similar to our results, Kolnik et al 22 showed that the prevalence of MEFV mutations in patients with HSP was not more than general population, but study of Dogan et al 18 showed that the prevalence of MEFV mutations was 9 fold more in HSP patients than general population. These different results may be attributed to genetic variations in different geographical areas.…”
Section: E148qsupporting
confidence: 82%
See 3 more Smart Citations
“…This finding probably indicates that M680I mutation may be a predisposing factor to HSP. Similar to our results, Kolnik et al 22 showed that the prevalence of MEFV mutations in patients with HSP was not more than general population, but study of Dogan et al 18 showed that the prevalence of MEFV mutations was 9 fold more in HSP patients than general population. These different results may be attributed to genetic variations in different geographical areas.…”
Section: E148qsupporting
confidence: 82%
“…22 In our study, although leukocytosis, elevated ESR, positive CRP and high platelet count were more frequent in patients carrying MEFV mutations, but this difference was not statistically significant. In the Kolnik et al 22 and Dogan et al studies 18 similar results were reported. However in the study of Ozcakar et al 23 ESR and CRP levels were significantly higher in the group with mutations.…”
Section: E148qsupporting
confidence: 78%
See 2 more Smart Citations
“…The MEFV gene is located in 16p13.3 and has 10 exons encoding a protein (pyrin/marenostrin) with multiple domains. To date, more than 80 different mutations in the MEFV gene have been recognized and several mutations in it are associated with the severity of diseases (5). Pyrin could only be found in granulocytes and is involved in inflammation and cell death regulation (5,6).…”
Section: Introductionmentioning
confidence: 99%